Elementary school teachers perspective about educative reform in Zacatecas, México - Elizabeth Cristina Bañuelos Sánchez; Josefina Rodríguez González; Lizeth Rodríguez González; Sergio Aguilar Reveles (Universidad del Magdalena, 2017)
The results of a research carried out in the state of Zacatecas, México, aiming at probing teachers perceptions about the Educative Reform (RE) to elementary school education approved in 2013 in the country are presented. Structural reforms served as the research theoretical frame and are the starting point to analyze changes that reorganized educative institutions in general. The information gathering was conducted by an interview with open answers, focusing on the aspects which have direct effects on teachers: evaluation, entry requirements and the job continuity. The results show that most teachers do not oppose the evaluation, provided that it is used as a tool for improving their teaching practice. Yet they do mistrust the transparency of the system, since they consider that the RE is a hidden mechanism to fire teachers, instead of a mechanism to improve the quality of education.